Identifikasi Sebaran Nikel Laterit dan Volume Bijih Nikel Menggunakan Korelasi Data Bor - Eltrit Bima Fitrian (Program Studi Teknik Sipil UKI Paulus-Makassar, 2021)
Nickel, which is one of the economical minerals found on earth, of course needs to know its distribution to be able to provide economic benefits and meet industrial demand, given the importance of nickel's function, which is very much needed by the world metal industry. The aim of this study were (1) to identify the spread of laterite nickel deposits in the mining area of ​​PT. Vale Indonesia, Sorowako East Luwu (2) to prepare large volumes of nickel ore for commercial exploration. To identify the distribution of nickel laterite, drill data is used, the drill data that has been obtained is processed by ArGcis 9.3 software to obtain the distribution area of ​​nickel deposits in the laterite layers. Then to see the cross-section of the nickel laterite layer in 3 dimensions used Surpac 6.1.2 software while to see the large volume of nickel ore, uses the Influence Area method. The distribution of nickel in the laterite layer is influenced by the topography and slope area of the research. Meanwhile, the calculation of the total volume of nickel ore obtained in each laterite layer is 2,913,682 m3.